Phase 1 study of TTC-352 in patients with metastatic breast cancer progressing on endocrine and CDK4/6 inhibitor therapy - Dudek, Arkadiusz Z.; Liu, Li C.; Fischer, James H.; Wiley, Elizabeth L.; Sachdev, Jasgit C.; Bleeker, Jonathan; Hurley, Randolph W.; Tonetti, Debra A.; Thatcher, Gregory R. J.; Venuti, Robert P.; O’Regan, Ruth M. (Breast cancer research and treatment, 2020)
Purpose TTC-352 is a selective human estrogen receptor (ER) partial agonist developed for treatment of hormone-refractory ER + breast cancer. Methods This was an accelerated dose escalation study with the primary endpoint of maximum tolerated dose that evaluated five dose levels of TTC-352 in breast cancer progressing after at least two lines of hormonal therapy including one in combination with a CDK4/6 inhibitor. The secondary objectives were to determine treatment tolerability, pharmacokinetics of TTC-352, best response, progression-free survival (PFS), and PKCα expression in tumors. Results The study enrolled 15 patients. No dose-limiting toxicity was observed. Patients experienced the following grade 3 toxicities: asymptomatic pulmonary embolism, diarrhea, aspartate transaminase elevation, and myalgia, and one grade 4 toxicity of gamma glutamyltransferase elevation. Pharmacokinetic half-life was 7.6–14.3 h. The intra- and inter-individual variability for AUC 0 -∞ hampered assessment of the relationship between dose and AUC 0 -∞. Median PFS was 58 days (95% CI = 28,112). Higher PKCα expression in tumor stroma was associated with a trend toward longer PFS. Conclusions TTC-352 demonstrates safety and early clinical evidence of antitumor activity against heavily pretreated hormone-refractory breast cancer. Based upon TTC-352 plasma concentrations and tolerability, the 180 mg twice a day is recommended for further testing. (ClinicalTrials.gov Identifier: NCT03201913)